Conceitos políticos na obra de Ortega y Gasset - Almeida, Antonio Charles Santiago (2009)
The dissertative proposal is guided in the sense of understanding the political concepts presented in the Ortega y Gasset work. For so much, it intends to identify them starting from an own logic that the author delineates in the formulation of its politicalphilosophical thought. Simultaneously, the relationship is looked for among Ortega y Gasset with other theoretical ones denominated of elitists, for example Gaetano Mosca, Vilfredo Pareto and Robert Michels. In that way, it is attempted to analyze if Ortega y Gasset has the same elitists theories and if the same is part of the elitist theoretical group. In that sense, the dissertation turns in two moments. In the first, it relates the Spanish philosopher with other theoretical ones to notice the consent and the disconsent among them and, after, to detect if there is structural singularity of the orteguiano thought or if Ortega y Gasset is in fact a elitist theoretical. Still on that moment, it intends to find the period in that Ortega y Gasset is placed and the socio-cultural dimensions that involve the author and its critical posture about problems that happened in 20th century. In the second moment, it is attempted an internal analysis of the work, The Masses Rebellion for the minorities and masses concepts of the structuring and systematization presented in the Quixote Meditations and Spineless Spain works. Being a bibliographical research, the discussion is grounded on a debate with several authors that referred the theme and they didn't drain it. Due to that, it is important to notice the Ortega y Gasset contributions in the debate that refer the politics notion and philosophy through the minorities and masses concepts